Berpikir dan Berperilaku dengan Rasa - Devi Kurniawati Homan (Humaniora, 2013)
Article discusses the importance for a designer to understand about psychology and consumers’ behaviors that act based on their feelings. Human as a complicated living creature has lot of feelings before making a reaction. The reaction itself is based on their own feeling from their experiences or the others’ before. In our daily life, we think a lot based on our feelings. We associate a stimulus with an unconscious physical or emotional response. A designer often needs to make a promotion, branding, and campaign for a product or something else. So, it is important for designers to know their targets and behaviors. By understanding their target behaviors, it is easier to predict or to design the reaction and response when the product or campaign is launched. The understanding of the psychology study is important for a designer as well as understanding the other branch of study beside their own study about aesthetics. When the designer understands a lot of things, they can make a creative, good and useful visual communication.